2019
DOI: 10.1017/jlg.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Debunking “pluri-areality”: On the pluricentric perspective of national varieties

Abstract: Pluricentric approaches to international varieties have been a mainstay in English dialectology since the 1980s, often implied rather than expressed. What is standard lore in many philologies is today questioned in one philology, however. This paper assesses the pros and cons of the so-called “pluri-areal” perspective, which has in the past few years become prominent in German dialectology. Intended to replace the pluricentric model, “pluri-arealist” perspectives affect the modelling of German standard varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
5
0
2
Order By: Relevance
“…Elspaß et al, 2017;Glauninger, 2013;Herrgen, 2015;Niehaus, 2015). Dollinger (2019aDollinger ( , 2019b viszont egy rendkívül részletes és mindenre kiterjedő viszontválaszban fogalmazza meg, miért nem jogos felvetés mégsem az államhatárok szerepének teljes elvetése, ezzel megvédve a többközpontú megközelítést. Anélkül, hogy a részletekbe bocsátkoznék, talán a legjobban úgy foglalhatnám össze Dollinger (2019aDollinger ( , 2019b álláspontjának a lényegét, hogy a határokon átívelő jelenségek alapján inkább a nemzeti változatok közötti átfedésekre, ill. átmeneti régiókra (mintegy pufferzónákra) érdemes következtetni.…”
Section: Problémák éS Megoldásokunclassified
“…Elspaß et al, 2017;Glauninger, 2013;Herrgen, 2015;Niehaus, 2015). Dollinger (2019aDollinger ( , 2019b viszont egy rendkívül részletes és mindenre kiterjedő viszontválaszban fogalmazza meg, miért nem jogos felvetés mégsem az államhatárok szerepének teljes elvetése, ezzel megvédve a többközpontú megközelítést. Anélkül, hogy a részletekbe bocsátkoznék, talán a legjobban úgy foglalhatnám össze Dollinger (2019aDollinger ( , 2019b álláspontjának a lényegét, hogy a határokon átívelő jelenségek alapján inkább a nemzeti változatok közötti átfedésekre, ill. átmeneti régiókra (mintegy pufferzónákra) érdemes következtetni.…”
Section: Problémák éS Megoldásokunclassified
“…As mentioned earlier, the notion of pluricentricity has recently been juxtaposed to 'pluriareality' especially in German linguistics (Dollinger, 2019a(Dollinger, , 2019b. Some linguists, for example Elspass et al (2017), showed that in the Germanspeaking area, syntactic choices are regionally distributed in a 'pluriareal' fashion, that is the same phenomena occur in several, mostly adjacent areas but these areas are totally independent of the state boundaries between Germany, Austria, and Switzerland.…”
Section: Perception or Production?mentioning
confidence: 99%
“…The notions of 'pluricentricity' and 'epicentral language varieties' are under discussion: with their emphasis on national boundaries and power relationships, they impose a decidedly conservative, nationally focused perspective and may actually therefore be regarded as somewhat untimely. This is epitomized in the recent debate on the relative merits of the concepts of 'pluricentricity' versus 'pluriareality' (Durgasingh & Meer, forthcoming;Dollinger, 2019aDollinger, , 2019bMuhr, 2020).…”
mentioning
confidence: 99%
“…The focus on linguistic formparticularly on lexical similarities across a continuous area which traverses national bordersdownplays the symbolic value of national standard varieties for expressing unity and shared social identity. The controversies over pluricentricity versus pluriareality have largely been confined to the domain of the German language, and it has been argued that the concept of pluriareality threatens how national standard varieties of German are valued and that the pluriareal approach adheres to an axiom of a single standard German (Dollinger 2019a(Dollinger , 2019b.…”
Section: Pluricentricity or Pluriarealitymentioning
confidence: 99%